ENVIRONMENTAL AND SOCIO-CULTURAL IMPACT OF TOURISM (Scientific journal of the Fergana State University, 2026)
Today international travelers are a large and growing proportion of tourism consumers. Travel to international destinations has been increasing at a fast pace. Over the last decades there has been an increasing awareness of the impact tourism has on the environment, societies, economy, culture in which tourism takes place. The economic impacts of tourism are not the only important impacts that must be considered when tourism development is proposed. Effects on environment, public, and cultures of a region are just as important to study and predict as the economic effects of tourism. Where tourism has grown dramatically many different positive and negative impacts have been found, and the greater the dependence on tourism the community has, the more inclined locals and the local tourist industry are to change local traditions and lifestyles to adapt to tourists’ needs. Therefore, it’s important to consider potential social and cultural impacts when planning for tourism.